Pemutusan Hubungan Kerja Secara Sepihak Berdasarkan UU Cipta Kerja (Studi Kasus Pada PT. Shopee Internasional Indonesia) - Guntur Putra Ramadhan; Muhammad Rizal; Sari Usih Natari (Universitas 45 Surabaya, 2023)
The purpose of this research is to understand the factors that lead to Termination of Employment (PHK) based on the Job Creation Law and to obtain legal protection for employees of PT. Shopee International Indonesia against layoffs in a unilateral way. This research also uses normative legal research methods through a conceptual and statutory approach with the support of both primary and secondary legal materials and uses techniques in qualitative analysis so that it can examine the problems that are currently happening in the field. The results of this study show that namely the case of PT. Shopee Internasional Indonesia as part of a unilateral layoff case by violating the provisions of the Job Creation Law. The absence of clear sanctions in the law provides an opportunity for companies to carry out layoffs in a unilateral way for employees. For workers who have been laid off unilaterally, they must receive a form of legal protection that is in accordance with the Job Creation Law, as well as the President's commitment to improving quality in the economic sector. Companies that carry out layoffs in a unilateral way must receive appropriate sanctions because they have violated the law and also the lack of fulfillment of various rights of citizens who should receive constitutional guarantees.